Spontaneous galvanic displacement of Pt nanostructures on nickel foam: Synthesis, characterization and use for hydrogen evolution reaction. (19th April 2018) - Milazzo, Rachela G.; Privitera, Stefania M.S.; D'Angelo, Daniele; Scalese, Silvia; Di Franco, Salvatore; Maita, Francesco; Lombardo, Salvatore
Abstract: In this paper we propose the use of spontaneous galvanic displacement as a promising solution to produce nickel foam electrodes functionalized with interconnected platinum nanoparticles. Scanning Electron Microscopy analyses, coupled with X-ray Energy Dispersive Spectroscopy show that, under proper conditions, we can overcome the limits of other deposition techniques, achieving a uniform Pt coverage throughout the 3D structure of the Ni foam. We show that such a condition, not deeply investigated in previous literature, turns out to be crucial for the long term stability of the electrodes under constant current stress. The amount of Pt on the Ni foam has been experimentally evaluated, obtaining optimal results with 0.015 mg cm −2 of noble metal in a 0.16 cm thick electrode. Such a low amount corresponds to a Ni foam cost increase of less than 0.1%. Graphical abstract: Highlights: Ni foam functionalized with Pt is proposed as a cathode for HER. Pt is deposited by spontaneous galvanic displacement (GD). Under optimized conditions the Ni electrode surface can be uniformly covered. A full coverage is crucial for long term stability under constant current stress.